Experimental and Numerical Analysis of Brake Disc Modal Behaviour - Kareem Abdulghafour Abdulla; Chalang Hamarasheed Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The aim of this study is to use numerical approaches, specifically FEA and MATLAB Simulink, and experimental modal analysis to investigate the structural dynamic behaviour of disc brakes; based on different wear thickness. The impact hammer test (a modal analysis excitation technique) has been performed to find out the brake disc structure modal parameters; particularly the brake disc's natural frequencies. Due to the fact that the measurements were made using the actual disc brake structure can be utilized to justify the natural frequency derived from finite element modelling. The disc brake rotors in this work has wear thicknesses of 0.5 mm, 1.0 mm, and 1.5 mm compared to their original thickness of 20 mm with weight of 4.20 kg. An impact hammer experiment is employed to obtain the modal parameters, such as natural frequency, damping ratio, and mode shape, under a free-free state. The first four natural frequencies for a disc brake rotor with its original thickness are 532 Hz, 525 Hz, and 521 Hz, and 538 Hz respectively. The results show that the natural frequency drops as the thickness reduction increases at the same mode. Since wear reduces the disc brake rotor's natural frequency, it can be inferred that this is one of the factors that might be causing the brake squeal issue. In addition, models examined by the MATLAB Simulink to find theoretically the natural frequency (or the resonant frequency; since the value of damping ratio is too small) of the process via bode plot criterion of stability. The results were near to those obtained practically.